Numerical and experimental study of crashworthiness parameters of honeycomb structures - Partovi Meran, Ahmad; Toprak, Tuncer; Muğan, Ata (Elsevier BV, 2014)
Abstract Crashworthiness parameters of aluminum hexagonal honeycomb structures under impact loads are investigated by using finite element methods and conducting experiments. To validate the finite element models, numerical results are compared with experimental measurements and theoretical results reported in literature. In numerical simulations of honeycomb structures, out-of-plane loads are considered while the aluminum foil thickness, cell side size, cell expanding angle, impact velocity and mass are varying, and dynamic behavior and crashworthiness parameters are examined. It is observed that there are good agreements between numerical, experimental and theoretical results. Numerical simulations predict that crashworthiness parameters depend on cell specification and foil thickness of the honeycomb structure and are independent of impact mass and velocity.